“PLAN DE MARKETING PARA EL SUPERMERCADO “MERCATOA” EN LA CIUDAD DE LOJA” - NARVÁEZ VALLEJO, ALLISON ELIZABETH (2019)
Currently, every organization requires the implementation of a marketing plan that allows it to have a connection between the company and the customer to attract and retain it, allowing through an analysis of the organization to know what its need is and consequently improve sales and profits of the company. It is so that competition is in the market constantly evolving, developing new ways to attract the customer to your company and on the contrary for those who lack a marketing plan run the risk of generating the decline of organizations, which is why the main problem of research is based on the absence of a marketing plan for the company, which does not allow optimal growth and benefit from their opportunities, because of it can not achieve their objectives and goals. Based on the problems mentioned above, this thesis has as a general objective: "MARKETING PLAN FOR THE SUPERMARKET "MERCHANDISE" IN THE CITY OF LOJA", among the specific objectives is found: Develop an internal and external analysis of the environment in which the Supermarket MERCATOA is located in order to identify strengths, weaknesses, opportunities and threats of the company, as well as conduct a market research to know the behavior of customers of the Supermarket MERCATOA, so that we identify their expectations in terms of needs, tastes, desires and prices, as well as establish marketing mix strategies to solve the difficulties presented by the company Supermarket Mercatoa. Thus, in order to respond to this, research methods were used, such as deductive, inductive, analytical, as well as research techniques for the collection of information such as direct observation, interviews with the manager and surveys carried out with 353 clients of the 6 company; following this, the corresponding information was put into analysis and when it was processed, the marketing plan proposal for the company was prepared. In addition, the whole process executed for the realization of the research topic is presented, which begins with the external analysis of the company, PEST analysis, competition analysis, as for the matrix of External Factors (EFE) results in 2.50 points, which shows to be stable and must focus its efforts on its opportunities. This is followed by basic data on the Supermarket "MERCATOA" as well as its location, organization, development of a situational diagnosis of the company where it allows an internal analysis, observing the resources with which it has such as suppliers, image, brand, subsequent to it is presented the analysis of the matrix of Internal Factors (EFI) with a result of 2.39 points, predominance of weaknesses over strengths, the SWOT analysis together with the High Impact Matrix, which allowed determining the strategic objectives for the company. In the most important conclusions we have that the Supermarket "MERCATOA", does not have a marketing plan defined for their needs, so it has not achieved its objectives, also the company has a poorly defined organizational design, so the staff does not know how to develop their activities efficiently, Also, the Supermarket "MERCATOA" does not have enough advertising to retain and loyalty to the customer, also does not offer any incentives for purchase amounts, also the company does not have directional signs of the location of products within the supermarket and this generates dissatisfaction and a bad shopping experience to the customer. Finally, at the conclusion of the study and evaluation of the external and internal situational analysis of the company, the following recommendations were determined: apply this Marketing Plan in order to take advantage of the opportunities that have been observed through analysis and improve the situation of the company, also apply the organizational redesign 7 proposed to improve the development of activities in the Supermarket "MERCATOA, apply the plan of advertising and promotion, so as to achieve a position in the market, rewarding the consumer with promotional items, with the aim of retaining, building loyalty and motivating a subsequent purchase, will also allow him to publicize the product lines and services offered and finally was recommended to implement the strategy of implementation of signs within the supermarket, to improve the shopping experience of the customer and avoid stress and loss of time of the consumer.